Control strategies of ice nucleation, growth, and recrystallization for cryopreservation. (1st January 2023) - Lin, Min; Cao, Haishan; Li, Junming
Graphical abstract: Abstract: The cryopreservation of biomaterials is fundamental to modern biotechnology and biomedicine, but the biggest challenge is the formation of ice, resulting in fatal cryoinjury to biomaterials. To date, abundant ice control strategies have been utilized to inhibit ice formation and thus improve cryopreservation efficiency. This review focuses on the mechanisms of existing control strategies regulating ice formation and the corresponding applications to biomaterial cryopreservation, which are of guiding significance for the development of ice control strategies. Herein, basics related to biomaterial cryopreservation are introduced first. Then, the theoretical bases of ice nucleation, growth, and recrystallization are presented, from which the key factors affecting each process are analyzed, respectively. Ice nucleation is mainly affected by melting temperature, interfacial tension, shape factor, and kinetic prefactor, and ice growth is mainly affected by solution viscosity and cooling/warming rate, while ice recrystallization is inhibited by adsorption or diffusion mechanisms. Furthermore, the corresponding research methods and specific control strategies for each process are summarized. The review ends with an outlook of the current challenges and future perspectives in cryopreservation. Statement of significance: Ice formation is the major limitation of cryopreservation, which causes fatal cryoinjury to cryopreserved biomaterials. This review focuses on the three processes related to ice formation, called nucleation, growth, and recrystallization. The theoretical models, key influencing factors, research methods and corresponding ice control strategies of each process are summarized and discussed, respectively. The systematic introduction on mechanisms and control strategies of ice formation is instructive for the cryopreservation development.